The Solomon Islands Hydrographic Unit (SIHU) - Bauer, Karl (The International Hydrographic Review, 2015)
This paper is aimed at creating an awareness of the development of the Solomon Islands Hydrographic Unit (SIHU) to the hydrographic community in general. It will briefly outline the geography and history of discovery of the Solomons leading to the formation of the SIHU which now produces four-colour charts to International Standards and carries out large scale surveys according to a five-year rolling plan.